2006
DOI: 10.2478/s11756-006-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotic BioPlus 2B on feed efficiency and metabolic parameters in swine

Abstract: The purpose of our work was to observe the influence of probiotic preparation BioPlus 2B on average daily gains of weaned pigs, feed efficiency and to evaluate some metabolic indices. The weaned pigs, at the age of 42 days, were included into the trial and divided into four groups. Pigs in groups A (n = 5) and B (n = 4) received BioPlus 2B also before weaning. Only group A received BioPlus 2B, at the concentration of 3.2 × 10 9 CFU per kg of feed, after weaning continually. Groups C (n = 5) and D (n = 4) did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Members of the genus Bacillus support natural intestinal microflora in the digestive tract, compete with undesirable microorganisms, and reduce the numbers of Enterococci, Bacteroides and coliforms (Ozawa et al, 1981;Adami and Cavazzoni, 1999;Kyriakis et al, 1999;Alexopoulos et al, 2001;Link et al, 2005;Link and Kovac, 2006) whilst Saccharomyces cerevisiae do not markedly alter the composition of host microflora (Mathew et al, 1998). These results are in contradiction to information provided by Mathew et al (1993Mathew et al ( , 1996 who observed changes in the microbial environment due to S. cerevisiae activity.…”
Section: Probioticsmentioning
confidence: 87%
See 1 more Smart Citation
“…Members of the genus Bacillus support natural intestinal microflora in the digestive tract, compete with undesirable microorganisms, and reduce the numbers of Enterococci, Bacteroides and coliforms (Ozawa et al, 1981;Adami and Cavazzoni, 1999;Kyriakis et al, 1999;Alexopoulos et al, 2001;Link et al, 2005;Link and Kovac, 2006) whilst Saccharomyces cerevisiae do not markedly alter the composition of host microflora (Mathew et al, 1998). These results are in contradiction to information provided by Mathew et al (1993Mathew et al ( , 1996 who observed changes in the microbial environment due to S. cerevisiae activity.…”
Section: Probioticsmentioning
confidence: 87%
“…The genus Bacillus, especially its members B. subtilis and B. licheniformis have been described to markedly reduce the severity of diarrhoea caused by E. coli (Adami and Cavazzoni, 1999;Kyriakis et al, 1999;La Ragione et al, 2001;Link et al, 2005) and at the same time improve growth parameters in weaned piglets (Roth et al, 1992b;Alexopoulos et al, 2001), whilst no improvement in health was observed after application of B. toyoi to sows and their piglets in a previous study (Martelli, 1992). However, Link and Kovac (2006) noted improvement in nutrient digestibility after feed supplementation with the same bacterium.…”
Section: Probioticsmentioning
confidence: 95%
“…1999; Alexopoulos et al. 2004a; Link and Kovac 2006), and therefore, is an alternative to antibiotic growth promoters (Kritas and Morrison 2005). One reason for using bacterial spores as feed additives is their stability.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria can participate in the process of digestion, through enhancing the digestive systems efficiency and ultimately improve the host growth. In particular, Bacillus subtilis and Bacillus licheniformis (as BioPlus 2B Ò product) have been successfully applied as probiotics for rainbow trout (Raida et al 2003;Bagheri et al 2008, Merrifield et al 2010, pig (Alexopoulos et al 2004;Link andKovac 2006), chiken (Rahimi andKhaksefifi 2006). It is the first time that this product is used in Artemia.…”
Section: Introductionmentioning
confidence: 99%